2021
DOI: 10.33545/gynae.2021.v5.i3b.911
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of preventive measures against coronavirus disease 2019 among pregnant women in a tertiary health facility in southwest Nigeria

Abstract: Introduction: The outbreak of corona virus disease (COVID-19) affects all categories of people and has resulted in death of several thousand of them all over the world including pregnant women. Various preventive strategies have been recommended to curb further spread of the disease thus limiting the morbidity and mortality of the disease. Objectives: This study assessed the knowledge, attitude, and practice of preventive measures against COVID-19among antenatal attendees in Ekiti State University Teaching Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
2
1
Order By: Relevance
“…Regarding the correlation between mothers’ knowledge and their practice, there was highly significant correlation at p value <.01**. This outcome was in same line with the study conducted by Aduloju et al, (2021) who founded that there was a positive and highly significant correlation between mothers’ knowledge and their practice at p -value <.01**. Also, Kunno et al, 2022 reported that there was correlation analysis performed that found a weak positive correlation between knowledge and practice scores ( r = 0.210, p -value = .01).…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the correlation between mothers’ knowledge and their practice, there was highly significant correlation at p value <.01**. This outcome was in same line with the study conducted by Aduloju et al, (2021) who founded that there was a positive and highly significant correlation between mothers’ knowledge and their practice at p -value <.01**. Also, Kunno et al, 2022 reported that there was correlation analysis performed that found a weak positive correlation between knowledge and practice scores ( r = 0.210, p -value = .01).…”
Section: Discussionsupporting
confidence: 89%
“…However, it is lower than a nding of studies conducted in china(71.0%) (42), India(92.7%) (39) and Pakistan (69.9%). (37).The nding of this study is also lower than some studies in Africa and Ethiopia like South Africa(76%)(36),Southwest Nigeria 79.2% (40) and Guraghe Zone, southern Ethiopia( 76.2%) (31). The nding of this study regarding the practice against COVID-19 by pregnant women is higher than a study conducted in Abakaliki, Nigeria (30.3%) (35).…”
Section: Socio-demographic Characteristicscontrasting
confidence: 57%
“…higher than studies conducted in South Africa(43.5%)(36), in Guraghe Zone, southern Ethiopia(54.84%) (31) and Debretabor town, northern Ethiopia(48.6%) (33). lower than studies in Pakistan(85.7%) (37), southwestern Iran(70%) (38) and India (75.3%) (39).This study is also lower than a study conducted in southwest Nigeria (87.2%) (40).…”
Section: Socio-demographic Characteristicsmentioning
confidence: 61%
“…Furthermore, 112 studies were excluded based on the exclusion criteria, such as the type of study, non-pregnant target group, and lack of access to the full text of the article. Finally, 53 studies, including 52 studies for knowledge [ 29 – 80 ], 15 studies for attitude [ 32 , 36 , 46 – 48 , 50 , 51 , 55 , 57 , 66 , 71 , 73 , 74 , 77 , 79 ], and 24 studies for practice [ 32 , 40 , 46 , 48 , 50 , 52 , 55 , 57 , 58 , 62 , 64 , 65 , 67 69 , 71 , 73 – 79 , 81 ] were included in this systematic review and meta-analysis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%